Coronary Computed Tomography Angiogram in Patients with Stable Chest Pain - Zhivka Stoykova (Journal of Biomedical & Clinical Research)
Using CT in patients with stable angina can help diagnose obstructive and non-obstructive coronary heart disease and improve the prognosis of patients. Purpose of this study was to compare the diagnostic accuracy of CT in patients with stable angina to conventional invasive angiography. A retrospective study of 142 consecutive patients with stable angina from 2005 to 2014 was conducted. All patients underwent CT coronary angiography and subsequent conventional angiography. Patients without significant stenosis but with typical anginal symptoms and over three risk factors for coronary heart disease, such as after PCI and ACB, and patients with CT evidence of significant coronary atherosclerosis were also included in this study. A contingency table was used to calculate sensitivity and specificity. The value of the cap was 0.610. The sensitivity of the methodology was 93% (CI 89% - 98%), the specificity 57% (CI 89% - 98%), the positive predictive value was 88%, and the negative predictive value was 73%. The high sensitivity, negative and positive predictive hundredth of CTA compared to conventional angiography suggest that this methodology is of great diagnostic value and opportunities to influence the clinical behavior and improve the prognosis.